Expanded carrier screening: what determines intended participation and can this be influenced by message framing and narrative information? - Voorwinden, Jan S (Eur J Hum Genet, 2017)
Next-generation sequencing enabled us to create a population-based expanded carrier screening (ECS) test that simultaneously tests for 50 serious autosomal recessive diseases. Before offering this test universally, we wanted to know what factors are related to intended participation and how the general public can be informed about the test without being influenced in their intention to participate. We studied this by measuring to what extent ‘message framing’ and ‘narrative information’ can influence people’s intended participation. Data were collected by means of an online survey of 504 potential users, and the factors examined were based on the Theory of Planned Behaviour and on previous research on intended participation in preconception carrier screening. Message framing was manipulated by explaining the risk of couple carriership in different ways, while narrative information was provided to only half of the respondents. The factors most positively related to intended participation were perceiving benefits of the screening, having a positive attitude towards the screening, having no religion, having an actual child wish and experiencing the choice to participate as easy. Perceived benefits and a positive attitude were most influential factors by far. Message framing and narrative information had no significant effect on intended participation, reinforcing that message framing and narrative information can help to inform the general public about ECS without influencing their intended participation. Future research should study if the importance of perceived benefits and a positive attitude can be replicated when other factors are included and when actual participation is measured instead of intended participation.